Cover Feature: Phosphate‐Templated Encapsulation of a CoII4O4 Cubane in Germanotungstates as Carbon‐Free Homogeneous Water Oxidation Photocatalysts (12/2021). Issue 12 (2nd June 2021) - Al‐Sayed, Emir; Nandan, Sreejith P.; Tanuhadi, Elias; Giester, Gerald; Arrigoni, Marco; Madsen, Georg K. H.; Cherevan, Alexey; Eder, Dominik; Rompel, Annette
Abstract : The Cover Feature shows the cobalt(II)‐substituted germanotungstate [Ge3 PCo9 (OH)5 (H2 O)4 W30 O115 ] 20− (Co9 ), which was obtained by a phosphate‐templated synthesis and exhibits high activity as a homogeneous water oxidation catalyst. More information can be found in the Full Paper by E. Al‐Sayed, S. P. Nandan, E. Tanuhadi, et al .